Hyperhashtag as a Component of the Interpretative Field of the Recipient in the Modern Media Space - Elizaveta S. Ens (Виртуальная коммуникация и социальные сети)
The present research featured the interdependent influence of the media space on modern society. Media affect one’s perception of environment and interpretation of reality. The article introduces the hypertext hypothesis about the essence of the new hyperhashtag phenomenon. The hyperhashtag is a word, phrase, abbreviation, etc., which is larger in meaning than the subsequent units. The verification experiment involved hyperhashtags elections, president, and deputy. The study also presents a new model of media text functioning. In the new context, the classical triad of author – text – recipient becomes a dualistic system in which the recipient predetermines the content of the selected text, and the hyperhashtag regulates this process. Therefore, the modern media space has a dual nature. On the one hand, it transmits information that affects the recipient’s worldview and partly determines it. On the other hand, the recipients affect what they are offered.